Preparation of Solid Lipid Nanoparticle-Containing Ovalbumin Based Reverse Micelle-Double Emulsion Technique - Khadijah Zai (Majalah Farmaseutik, 2023)
Encapsulation of protein in the lipid-based nanoparticle is quite challenging. A reverse micelle-double emulsion method could be used for answering this challenge because reverse micelles able to protect the polar core in a nonpolar solvent. Thus, the protein solution can be kept in the interior of the reverse micelle particle and hosted in a lipid matrix of nanoparticles. Herein, we describe the preparation of solid lipid nanoparticles (SLNp) for the encapsulation of ovalbumin (Ova) with reverse micelle-double emulsion. Using several combinations of solid lipids and phospholipids, we prepared SLNp containing Ova-reverse micelle. The optimized formulation enabled the incorporation of Ova in the solid lipid matrix of SLNp with nano size and narrow particle size distribution (PdI), and high entrapment efficiency for Ova. The particle size and zeta potential were measured by a dynamic light scattering spectrophotometer 214.8±15.94 nm and −3.44±0.21 mV, respectively. The entrapment efficiency (EE%) was determined by Spectrofluorometer by determining the quantitative of Ova-FITC labeling was 98.97±0.89%.